2006
DOI: 10.1210/jc.2006-0099
|View full text |Cite
|
Sign up to set email alerts
|

Small Changes in Thyroxine Dosage Do Not Produce Measurable Changes in Hypothyroid Symptoms, Well-Being, or Quality of Life: Results of a Double-Blind, Randomized Clinical Trial

Abstract: Small changes in T(4) dosage do not produce measurable changes in hypothyroid symptoms, well-being, or quality of life, despite the expected changes in serum TSH and markers of thyroid hormone action. These data do not support the suggestion that the target TSH range for the treatment of primary hypothyroidism should differ from the general laboratory range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 25 publications
2
73
0
7
Order By: Relevance
“…For example, a study on the starting dose of L-T 4 in newly diagnosed hypothyroidism found a faster normalization of thyroid parameters with a high starting dose of L-T 4 compared with an incremental dose regimen, but did not find a faster improvement of QOL (30). Two studies on the influence of small changes in L-T 4 doses, and thus TH levels, could not find changes in well-being, hypothyroid symptoms, or QOL (15,31). Our findings could have consequences for clinical practice as more than often L-T 4 dosages are adjusted based on the suggested relationship of patient complaints about QOL and TH levels just within or outside the normal reference range.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study on the starting dose of L-T 4 in newly diagnosed hypothyroidism found a faster normalization of thyroid parameters with a high starting dose of L-T 4 compared with an incremental dose regimen, but did not find a faster improvement of QOL (30). Two studies on the influence of small changes in L-T 4 doses, and thus TH levels, could not find changes in well-being, hypothyroid symptoms, or QOL (15,31). Our findings could have consequences for clinical practice as more than often L-T 4 dosages are adjusted based on the suggested relationship of patient complaints about QOL and TH levels just within or outside the normal reference range.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear that targeting the lower end of the TSH reference range will achieve patients' desired outcomes. The observational literature is divergent, and there is only one controlled trial addressing this, which did not show significant effects (11,(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Так, в ра бо те J.P. Walsh и со авт. [24] на зна че ние не сколь ко боль шей до зы L T 4 спо соб ст-во ва ло за ко но мер но умень ше нию ТТГ, а так же сни-же нию уров ня об ще го хо ле с те ри на (ОХС) у жен щин с ги по ти ре о зом. Од на ко на се го дняш ний день нет до ста точ ных ос но ва ний ре ко мен до вать всем па ци ен-там на зна че ние за ме с ти тель ной до зы L T 4 , обес пе чи-ва ю щей уро вень ТТГ в ниж нем ди а па зо не зна че ний.…”
Section: ис то рия за ме с ти тель ной те ра пии ги по ти ре о заunclassified